PERAN SELF-EFFICACY DALAM PENGGUNAAN TEKNOLOGI INFORMASI DI KONTEKS PENDIDIKAN: STUDI KASUS DI SMKN 1 KUPANG BARAT - Dortean Amelia Jois Jaha; Christmas Prasetia Ate (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
This research examines the role of self-efficacy in the use of information technology at SMKN 1 Kupang Barat. The study adopts a mixed methods approach, combining qualitative case study with quantitative methods using Likert scales. Participants include teachers and students actively using information technology in their learning processes. The research findings indicate varying levels of self-efficacy among participants, with the majority of teachers demonstrating high self-efficacy due to training and school management support. Students exhibit diverse levels of self-efficacy influenced by prior experience and access to devices. Analysis of the Likert scale questionnaires indicates a positive perception towards the use of technology in enhancing learning quality and preparing students for the future. Practical implications of this study include the necessity for ongoing teacher training, school management support, and optimization of technological resources to enhance the integration of information technology in learning at SMKN 1 Kupang Barat. Additionally, the study offers guidelines for the development of more effective educational policies in the future.